ACCURACY, READABILITY AND ACCEPTABILITY IN THE TRANSLATION OF ANDROID XIAOMI REDMI NOTE 4 - Prasetya, Irfan Zahid; Hartono, Rudi; Yuliasri, Issy (Universitas Negeri Semarang, 2019)
Android translation(s) were translated by multiple people/agencies during multiple period of times, thus they are very prone to accuracy, readability and acceptability errors. Based on that reason, I conducted this research to (1) analyze and find out the accuracy of the translation in Xiaomi Redmi Note 4 smartphone, (2) readability of the translation of the smartphone, and (3) the acceptability of the translation. The result of this study showed that all of the accuracy, readability and acceptability of the original translation showed worse results than the modified translation. For accuracy, Goff-Kfouri’s and Nababan’s rubric both showed better result for the modified translation. For readability by the translators, the average of original translation got 2.3 (negative) and modified got 3.8 (positive); whereas the end-users rated 2.4 (negative) and 3.8 (positive) respectively. For acceptability, the average of original translation by the translators was rated 2.6 (negative) and the modified translation got 3.7 (barely positive); and by the end users, the rates were 2.7 (negative) and 3.7 (positive).